Characterization of biodiesel fuel and its blend after electromagnetic exposure. Issue 1 (1st January 2017) - Nufus, Tatun Hayatun; Setiawan, Radite Praeko Agus; Hermawan, Wawan; Tambunan, Armansyah Halomoan
Abstract: It has been known that magnetic exposure of fuel prior to combustion can improve effectiveness of combustion process. However, the main reason of the phenomenon is still unclear. In this paper, characteristics of fuel as exposed to electromagnetic field was measured experimentally and inter-related appropriately in order to have preliminary insight to the clarification of the phenomenon. Fuel characteristics being investigated were viscosity, vibration of the fuel molecules, dipole moment, and refractive index. These experiments were performed using various blend compositions between fossil diesel (petrodiesel) and biodiesel fuel i.e. B0, B10, B40, B70 and B100. The electromagnetic field was generated by a galvanum tube wounded with 9, 000 wire coil. The fuel characteristics of both prior and post electromagnetic exposures were then measured with time variation of 0–1, 800 s. The experimental results revealed that electromagnetic exposure of the fuel increased vibrational frequency of its molecules significantly, which in turn weakened the attracting energy and caused uniform arrangement of dipole moment of the molecules. The experimental data also revealed that the fuel characteristics did not alter significantly after it was exposed to the electromagnetic field for more than 1, 200 s. This information is considered to be useful for further research in order to resolutely clarify the phenomenon of efficient combustion process of fuel after exposure to magnetic field.